Widespread use of herbal medicines by people living with human immunodeficiency virus and contamination of herbal medicines with antiretrovirals in Nigeria. (March 2019) - Gini, J; Amara, A; Penchala, Sujan D; Back, David J; Else, L; Egan, D; Chiong, J; Harri, Bala I; Kabilis, Elkanah D; Pama, Paul P; Stephen, M; Khoo, Saye H
Herbal medication use amongst people living with human immunodeficiency virus (PLWH) is widespread and understudied. This study aimed to evaluate the prevalence of herbal medicine use amongst PLWH and possible contamination with antiretrovirals (ARVs). Countrywide collection of herbal samples sold by street vendors in Nigeria for the following indications: human immunodeficiency virus (HIV), acquired immune deficiency syndrome, fever and general weakness. Samples were screened using a validated liquid chromatography-mass spectrometry/mass spectrometry method for the presence of the following ARVs: efavirenz, nevirapine, lopinavir, darunavir, ritonavir, atazanavir, emtricitabine, tenofovir and lamivudine. A survey was conducted among 742 PLWH attending four HIV clinics in Nigeria. Data were collected using a structured questionnaire and analysed using IBM SPSS statistics version 22.0 (IBM Corp., 2013, Armond, NY). Of the 138 herbal medicines sampled, three (2%) contained detectable levels of tenofovir, emtricitabine and/or lamivudine. Additionally, of the 742 PLWH surveyed, 310 (41.8%) reported herbal medicine use. Among the users, 191 (61.6%) started taking herbals after commencing HIV therapy while herbal medicine use preceded ARVs treatment in 119 (38.4%) PLWH. We found herbal use to be widespread among PLWH in Nigeria, with increasing use after commencing ARV. Three herbal preparations were also found to contain detectable levels of ARVs. This is a concern and should be studied widely across the region and countries where herbal medicine use is prevalent and poorly regulated.